PENGEMBANGAN MODEL CASE CONFERENCE PADA ANAK BERKEBUTUHAN KHUSUS - Dindin Rosyidin; Zulfitria Zulfitria; Dirgantara Wicaksono (Instruksional, 2020)
Each of children with special need in Labschool FIP UMJ is assisted by classroom teacher, assistant teacher, shadow teacher, and some therapists in his house. They have their own program and achievement so that it can cause overlapping among them.  Thus it is necessary to develop and integrate a holistic model and integrated program to handle children with special needs.  The study provides the development of Case Conference Model at children with special need. The study used research and development (R&D). The model used in the study is ADDIE model. It stands for  analysis, design, develop, implement, and evaluate. The population in the study is special need’s children at Labschool FIP UMJ. The output of the study is case conference model which can be used for children with special need.  The implementation of Case Conference model can help teacher, shadow teacher, parents and principle in dealing with special need’s children.